Evaluation of tomato (Lycopersicon esculentum L.) variety tolerance to foliar diseases at Kenya Agricultural Research Institute Centre-Kitale in North west Kenya - Anastacia, Masinde A. O.; Thomas, Kwambai K.; Hilda, Wambani N. (Global Journal of Food and Agribusiness Management, 2012)
Most vegetable cultivar evaluation trials focus on yield and quality attributes. However, disease tolerance is not routinely evaluated along with other parameters. The objective of this study was to evaluate new tomato cultivar for yield, quality and tolerance to foliar diseases. The most ubiquitous and devastating pathogen that infects tomatoes in the North rift Kenya is Phytophthora infestans that causes late blight and Alternaria solani that causes early blight. There are several disease management practices that can be implemented to manage this disease including rotation, mulching, spacing, fungicide applications, and use of tolerant varieties. This study aimed at testing different varieties. Six new tomato cultivars, TKA143-33, TKA158-6, TKA193-28, TKA155-18, TKA193-2, TKA195-43 alongside a local check, CALJ were evaluated. The trial was laid out in completely randomized Block design (RCBD) layout replicated four times. The results showed that there were significant differences among varieties during the long season but not short rain season on yield. The local check CAL-J gave the least yield. There was low incidence of foliar diseases on the newly introduced varieties. This suggests that some of the new varieties could be good candidates for long and short season production seasons.